A new species of Dendrobium sect. Crinifera (Dendrobieae) from Thailand - Pedersen, Henrik Æ. (2026)
A new species of Dendrobium sect. Crinifera is described from Thailand. The late Peter O’Byrne is appropriately credited for his important preparatory work for our study and for coining the name of the new species, D. krabiense. Apparently endemic to southern Thailand, D. krabiense is similar to D. pardalinum but differs in the lip mid-lobe being distinctly clawed and in the lip ornaments only consisting of two lateral keels that extend from near lip base to claw of mid-lobe. Dendrobium krabiense is also similar to D. phuketense but differs in having larger, spotted flowers with a proportionally longer mentum. The material here referred to D. krabiense was previously misidentified as Flickingeria pallens (now considered a synonym of D. pardalinum).